2006
DOI: 10.1007/s10529-006-9051-5
|View full text |Cite
|
Sign up to set email alerts
|

Kinetic Studies of Reactive Azo Dye Decolorization in Anaerobic/aerobic Sequencing Batch Reactors

Abstract: The decolorization kinetics of Remazol Brilliant Violet 5R (RBV-5R) and Remazol Black B (RB-B) (mono- and diazo reactive dyes, respectively) was investigated in the first 9 h (anaerobic phase) of a 24-h cycle anaerobic/aerobic sequencing batch reactor (SBR). Two distinct, successive decolorization periods were observed for both dyes, apparently due to different decolorization mechanisms. The apparent first-order rate constants were much lower for the second periods. First-order kinetics were apparently followe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(14 citation statements)
references
References 13 publications
1
12
0
Order By: Relevance
“…3a, or in a continuous system in separate vessels (Fig. 3b) (Wang et al 2009;Glässer et al 1992;Tan 2001;Lourenço et al 2006).…”
Section: Anaerobic/aerobic Treatment Of Azo Dyesmentioning
confidence: 99%
“…3a, or in a continuous system in separate vessels (Fig. 3b) (Wang et al 2009;Glässer et al 1992;Tan 2001;Lourenço et al 2006).…”
Section: Anaerobic/aerobic Treatment Of Azo Dyesmentioning
confidence: 99%
“…This may have occurred because of evaporation in the cathode layer. The Previous studies have suggested that azo dyes cannot be decolorized at the cathode because of the high oxidation-reduction potential of the cathode (Li et al, 2010;Lourenço et al, 2006). However, in this study, there was a thin anoxic layer in the bottom of the cathode that provided conditions favorable to decolorization.…”
Section: Figure 5 Is Herementioning
confidence: 63%
“…Initial dye concentrations of 800, 1600, and 3200 mg/L resulted in decreased cumulative CH 4 production by 57, 58, and 88%, respectively. The anaerobic dye reduction rates of reactive azo dyes were relatively high [43,44] when compared to methanogenesis rates. Therefore, the reduction products of HRO107 may have inhibitory effects on the methanogenic culture throughout the assays together with virgin HRO107.…”
Section: Effect Of Dye On Ws Digestion In Unacclimated and Acclimatedmentioning
confidence: 95%